Foraging Benefits of Ecological Cognition in Fruit-Eating Primates: Results From Field Experiments and Computer Simulations - Janson, Charles H. (Frontiers in Ecology and Evolution, 2019)
I focus on the foraging efficiency (food intake per time) of a hypothetical forager that uses distinct levels of information about a set of discrete renewing resources. The information may be the distance to the resource (D), both distance and maximum productivity of the resource (DP), or distance, productivity, and the elapsed time since the forager last visited each resource (DPT). The expected foraging efficiencies are based on the results of a field experiment on wild capuchin monkeys (Janson 2016) that documented the use of integrative memories of resource location, productivity, and elapsed time since the previous visit. Computer simulations of the choice process are used to extend the resource parameter space beyond the field experiment. The goal is to explore to what extent the use of elapsed time in choosing discrete feeding sites is a benefit under various conditions of resource and consumer characteristics. Major findings include that the use of elapsed time generally increases foraging efficiency on renewing resources by 30-35%, without much effect of resource size or variability – indeed, DPT outperforms D or DP choice even when all resources have the same productivity. The relative benefit of DPT increases when the most productive resources are only moderately common (not so rare that they contribute little to food intake, nor so common that choosing the nearest resource is likely to arrive at a highly productive one). The relative benefit of DPT decreases when the forager’s gut capacity is small or gut passage time is long because it cannot fully ingest large resource accumulations that occur after long elapsed intervals. I suggest that memory for and use of elapsed intervals since prior visits in foraging choices will prove to be a common feature of diverse foraging animals whenever the presence of a forager depresses food availability in a local area.